Perencanaan Struktur Dermaga Peti Kemas Kapet Batulicin, di Kalimantan Selatan - Zainal Abidin; Fahrurarid .; Bambang Kiswono (Universitas Muhammadiyah Surabaya, 2018)
AbstractThe KAPET Batulicin area which has been designated as a National Strategic Area (NSA) based on PP No.26 of 2008, has the potential to develop superior commodities based on natural resources, especially plantations, production forests, iron or mining, and aquaculture and capture. But unfortunately the infrastructure (port), especially the port serving containers is still unavailable. The existing port is a port that serves coal transportation and is owned by private parties. So it is necessary to plan a container dock that is expected to be able to support economic progress and prosperity in the Batulicin region. This dock is planned to be able to serve container ships with a maximum draft of 50,000DWT. This type of dock structure is an open wharf with trestle as a link between the stacking field and the pier. Pile foundation using JIS A 5525 steel piles. In planning this dock structure, the structural system is analyzed using the SAP2000 program with 3D models. The loading and reinforcement of the structure is controlled based on SNI regulations and BMS 1992. From the results of the design planning is obtained, the dock consists of a jetty head building and 2 trestles. The dimensions of the jetty head are 720m long and 50m wide. The dimensions of the pier beam are 80cm wide and 120cm high, while the pile dimensions are 1016mm diameter, 19mm thick and 20.65m long for upright piles and 20.75m for tilting piles with 6V: 1H slope ratio. The pile cap dimension for a single pole is 1.5x1.5x1.2 m. Pile cap dimensions for double poles are 3x1,4 x1,4 m. The structure used is the fender type V 400 H and the BR-150 bollard structure.Keywords: Port, Dock, Container, PileAbstrakWilayah KAPET Batulicin yang telah ditetapkan sebagai Kawasan Strategis Nasional (KSN) berdasarkan PP No.26 Tahun 2008, memiliki potensi pengembangan komoditas unggulan berbasis pada sumber daya alam, terutama perkebunan, hutan produksi, pertambangan bijih besi, serta perikanan budidaya dan tangkap. Namun sayangnya prasarana (pelabuhan) khususnya pelabuhan yang melayani peti kemas masih belum tersedia. Adapun pelabuhan yang sekarang ada merupakan pelabuhan yang melayani pengangkutan batu bara dan meruapakan milik pihak swasta. Sehingga perlu adanya perencanaan dermaga peti kemas yang diharapkan akan mampu menunjang kemajuan perekonomian dan kesejahteraan di wilayah Batulicin. Dermaga ini direncanakan mampu melayani kapal petikemas dengan draft kapal maksimal 50.000DWT. Tipe struktur dermaga ini adalah wharf terbuka dengan trestle sebagai penghubung antara lapangan penumpukan dengan dermaga. Tiang pondasi menggunakan tiang pancang baja JIS A 5525. Dalam perencanaan struktur dermaga ini, sistem struktur dianalisis dengan menggunakan program SAP2000 dengan model 3D. Pembebanan dan penulangan struktur dikontrol berdasarkan peraturan SNI dan BMS 1992. Dari hasil perencanaan desain didapatkan, dermaga terdiri dari bangunan jetty head dan 2 buah trestle. Dimensi dari jetty head yaitu panjang 720m dan lebar 50m. Dimensi balok dermaga yaitu lebar 80cm dan tinggi 120cm, sedangkan dimensi tiang pancang diameter 1016mm, tebal 19mm serta panjang 20,65m untuk tiang pancang tegak dan 20,75m untuk tiang pancang miring dengan perbandingan kemiringan 6V : 1H. Dimensi pile cap untuk tiang tunggal yaitu 1,5x1,5x1,2 m. Dimensi pile cap untuk tiang ganda yaitu 3x1,4 x1,4 m. Pada struktur sandar yang dipakai adalah Fender tipe V 400 H L=200 serta struktur bollard BR-150.Kata kunci: Pelabuhan, Dermaga, Petikemas, Tiang pancang